The Study of Brown Rice Starch Effect On Hydroxyapatite Composites - F. Mohd Nasir, N; Sucinda, A; M Cheng, E; S. Abdul Majid, M; A.M. Amin, N; Rahim, Robbi; Jusoh, M; F. Abdul Khalid, M (International Journal of Engineering and Technology, 2018)
The fabrication of starch-hydroxyapatite (HA) scaffolds was conducted previously by using corn, tapioca and rice. Here, local brown rice was chosen as the source of starch since different type of rice may give different outcome of in term of the scaffoldâ€™s materials characteristics. The main aim of this study is to obtain a brown rice starch-hydroxyapatite (HA) composite scaffolds that could imitate the structure and the characteristics of a natural bone. The fabrication process involved solvent casting and particulate leaching method which using NaCl as a porogen agent. Four ratios of starch-HA were fabricated with concentration of starch 50wt%, 60wt%, 70wt% and 80wt%. Afterward, the effects of the brown rice starch on the scaffolds were investigated by water absorption test and Scanning Electron Microscope (SEM). Here, only 50wt% and 60wt% ratio of starch-HA can be used to fabricate tissue scaffolds using solvent casting and particulate leaching method. Hence, the 60wt% ratio scaffolds has the highest water absorption of all and the poreâ€™s size observed through SEM corresponded to this. The FTIR also shows there are more interactions between Brown Rice starch and HA for the 60wt% ratio.Â Â